The Effect of SAP Implementation, The Clarity of The APBD And SPIP on LAKIP in North Sumatra Province - Syakilla, Alya An Nais; Putri, Bela Amanda; Ramadhana, Tri; Wulandari, Windi; Irawan (CV Raskha Media Group, 2025)
The purpose of this study is to analyze the effect of the implementation of Government Accounting Standards (SAP) and the clarity of the Regional Revenue and Expenditure Budget (APBD) on the Government Internal Control System (SPIP) as a mediating variable. This study confirms that the implementation of SAP and the clarity of APBD together contribute to improving the quality of SPIP, and in the long term have a positive impact on the quality of LAKIP. Local governments that want to improve performance accountability must pay attention to the consistent application of SAP, prepare the APBD with measurable performance indicators, and strengthen the SPIP so that all processes can run with adequate internal supervision. Thus, the quality of LAKIP can continue to be improved as a form of transparency and public accountability. This study uses a quantitative approach with primary data obtained through a questionnaire using a 1–5 Likert scale. The research respondents consisted of local government officials involved in financial reporting, budget planning, internal supervision, and LAKIP preparation. Data processing was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software.